2021
DOI: 10.1101/2021.09.09.459396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong and specific connections between retinal axon mosaics and midbrain neurons revealed by large scale paired recordings

Abstract: The superior colliculus (SC) is a midbrain structure that plays important roles in visually guided behaviors. Neurons in the SC receive afferent inputs from retinal ganglion cells (RGC), the output cells of the retina, but how SC neurons integrate RGC activity in vivo is unknown. SC neurons might be driven by strong but sparse retinal inputs, thereby reliably transmitting specific retinal functional channels. Alternatively, SC neurons could sum numerous but weak inputs, thereby extracting new features by combi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…Our approach cannot obtain some RGC types that do not send their axons to OT, such as the one projecting to the suprachiasmatic nucleus via the retinohypothalamic tract (Li and Schmidt, 2018). Nevertheless, the fact that we obtained diverse types of visual responses, better than previous in vivo studies (Hong et al, 2018; Liang et al, 2018; Schröder et al, 2020; Sibille et al, 2021) if not all the ∼30 RGC types observed ex vivo (Baden et al, 2016; Jouty et al, 2018), validates our recording methods to monitor retinal outputs in vivo .…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Our approach cannot obtain some RGC types that do not send their axons to OT, such as the one projecting to the suprachiasmatic nucleus via the retinohypothalamic tract (Li and Schmidt, 2018). Nevertheless, the fact that we obtained diverse types of visual responses, better than previous in vivo studies (Hong et al, 2018; Liang et al, 2018; Schröder et al, 2020; Sibille et al, 2021) if not all the ∼30 RGC types observed ex vivo (Baden et al, 2016; Jouty et al, 2018), validates our recording methods to monitor retinal outputs in vivo .…”
Section: Resultssupporting
confidence: 72%
“…We next asked if RGC responses differ between in vivo and ex vivo conditions. This is a critical comparison because retinal physiology has been mostly studied and best characterized in an isolated preparation (Gollisch and Meister, 2010;Sanes and Masland, 2015), but little is known about it in awake animals (Weyand, 2007;Liang et al, 2018Liang et al, , 2020Schröder et al, 2020;Sibille et al, 2021). Here we exploited stimulus ensemble statistical techniques ("reverse correlation"; Meister et al, 1994;Chichilnisky, 2001) to systematically characterize the visual response properties and make a direct comparison across different recording conditions in the linear-nonlinear cascade model framework (see Methods for details).…”
Section: Comparison Of Retinal Output Properties Between In Vivo and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…A fundamental question is then if RGC axons can nevertheless find precise targets even after they get “lost” in the long-range projection (Figure 1A), or if target neurons need to reconstruct the topography by elaborating local circuitry (Figure 1B). A recent study using Neuropixel probes has demonstrated a more precise one-dimensional mapping of RGC projections to the mouse SC surface (Sibille et al, 2021); however, local two-dimensional (2D) organizations of RGC axons remain elusive in any retinorecipient area because such long-range projections of dense axonal fibers preclude a precise anatomical characterization of the projection patterns at a single-cell resolution (Hong et al, 2011).…”
Section: Mainmentioning
confidence: 99%